Hépato-toxicité médicamenteuse : synergie d’action hépatotoxique des antirétroviraux, des antituberculeux, et d’antifongiques - essad, ayoub; Atbib, Yassine; berdi, fadoua; Tadlaoui, Yassina; Bousliman, Yassir (Jour Med Resh and Health Sci, 2022)
Although AIDS reduces the life expectancy of HIV positive patient due to opportunistic diseases. Medication management is also of significant impact, if one realizes the drug interactions that can take place between the different therapeutic protocols. Here we are talking about a 65 year old patient with HIV positive, tuberculosis and fungal infection.